2018
DOI: 10.1016/j.bbagrm.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptional control of macrophage miRNA signature via inflammation responsive enhancers revealed using a combination of next generation sequencing-based approaches

Abstract: MicroRNAs are important components of the post-transcriptional fine-tuning of macrophage gene expression in physiological and pathological conditions. However, the mechanistic underpinnings and the cis-acting genomic factors of how macrophage polarizing signals induce miRNA expression changes are not well characterized. Therefore, we systematically evaluated the transcriptional basis underlying the inflammation-mediated regulation of macrophage microRNome using the combination of different next generation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…ncRNAs are grouped into two major classes according to their size: small ncRNAs (<200 nucleotides) and long ncRNAs (≥200 nucleotides). MicroRNAs (miRNAs; 19–22 nucleotides) have been proven to regulate the expression of many genes and signaling pathways in autoimmune diseases, such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and multiple sclerosis (MS) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ncRNAs are grouped into two major classes according to their size: small ncRNAs (<200 nucleotides) and long ncRNAs (≥200 nucleotides). MicroRNAs (miRNAs; 19–22 nucleotides) have been proven to regulate the expression of many genes and signaling pathways in autoimmune diseases, such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and multiple sclerosis (MS) …”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs; 19-22 nucleotides) have been proven to regulate the expression of many genes and signaling pathways in autoimmune diseases, such as systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and multiple sclerosis (MS). [4][5][6] The other major type of ncRNA, lncRNAs, has recently received extensive attention due to their potential functions. lncRNAs are non-protein-coding RNA transcripts longer than 200 nucleotides that can interact with proteins, DNA, and RNA.…”
Section: Introductionmentioning
confidence: 99%
“…() reported that miR‐21 was an important contributor for promoting vascular inflammation, and the loss of miR‐21 would result in less inflammatory phenotype and help attenuate stent‐induced inflammatory vascular disease. MiR‐130a, miR‐132‐3p, let‐7b, miR‐155, miR‐146a, let‐7d‐5p, miR‐221, miR‐222, and miR‐144 have also been associated with inflammatory gene regulation, and certain human health problems and diseases such as metabolic syndrome, epilepsy, brain injury of intracerebral hemorrhage (Czimmerer et al., ; Marques‐Rocha et al., ; Srivastava, Dixit, Banerjee, Tripathi, & Sarat Chandra, ; Yu et al., ). MiR‐130a, miR‐132, miR‐155, and miR‐221 are found to be able to regulate the toxicity of mycotoxins (Croston, Lemons, Beezhold, & Green, ; Qi et al., ; Valencia‐Quintana et al., ).…”
Section: Mirna and Diseases: Are They Related To Mycotoxins?mentioning
confidence: 99%
“…Under peripheral inflammation, DRG neurons are stimulated by inflammatory mediators, which sensitize neurons for pain perception by altering the expression of many genes [12][13][14][15][16]. Since changes in the expression of some genes during inflammation are associated with chromatin reorganization [17], it was interesting to assess the extent of such reorganization in DRG neurons caused by inflammation.…”
Section: Introductionmentioning
confidence: 99%